Amoxicillin–Clavulanate-Induced Liver Injury - deLemos, Andrew S.; Ghabril, Marwan; Rockey, Don C.; Gu, Jiezhun; Barnhart, Huiman X.; Fontana, Robert J.; Kleiner, David E.; Bonkovsky, Herbert L. (Digestive diseases and sciences, 2016)
Background and Aims Amoxicillin–clavulanate (AC) is the most frequent cause of idiosyncratic drug-induced injury (DILI) in the US DILI Network (DILIN) registry. Here, we examined a large cohort of AC-DILI cases and compared features of AC-DILI to those of other drugs. Methods Subjects with suspected DILI were enrolled prospectively, and cases were adjudicated as previously described. Clinical variables and outcomes of patients with AC-DILI were compared to the overall DILIN cohort and to DILI caused by other antimicrobials. Results One hundred and seventeen subjects with AC-DILI were identified from the cohort ( n = 1038) representing 11 % of all cases and 24 % of those due to antimicrobial agents ( n = 479). Those with AC-DILI were older (60 vs. 48 years, P < 0.001). AC-DILI was more frequent in men than women (62 vs. 39 %) compared to the overall cohort (40 vs. 60 %, P < 0.001). The mean time to symptom onset was 31 days. The Tb, ALT, and ALP were 7 mg/dL, 478, and 325 U/L at onset. Nearly all liver biopsies showed prominent cholestatic features. Resolution of AC-DILI, defined by return of Tb to <2.5 mg/dL, occurred on average 55 days after the peak value. Three female subjects required liver transplantation, and none died due to DILI. Conclusion AC-DILI causes a moderately severe, mixed hepatocellular–cholestatic injury, particularly in older men, unlike DILI in general, which predominates in women. Although often protracted, eventual apparent recovery is typical, particularly for men and usually in women, but three women required liver transplantation.